2012
DOI: 10.1007/s13320-012-0049-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of transmission characteristics of tilted long period fiber gratings with full vector complex coupled mode theory?

Abstract: Based on the full vector complex coupled mode theory, a detailed analysis is made on the transmission spectrum characteristics of tilted long period fiber gratings. New transmission peaks are observed, which are located beside the long wavelength side of each transmission peak in the transmission spectrum of normal long period fiber gratings. The emerging transmission peaks are quite sensitive to both the grating tilted angle and the surrounding refractive index, and the corresponding relationship is discussed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Research about TFBGs from J. Albert's group has revealed the cladding modes coupled from a TFBG were split into two sets of polarization dependence cladding modes (TE and TM mode) [3,[18][19][20]. In addition to TFBGs, there were also several papers which have given theoretical modeling about the transmission spectra of tilted gratings with long period pattern [21,22]. Recently, Mou et al have published a review chapter about sensing applications using Ex-TFGs [23], and we have reported a high Q factor and sensitivity glucose sensor by using an Ex-TFG [24].…”
Section: Introductionmentioning
confidence: 99%
“…Research about TFBGs from J. Albert's group has revealed the cladding modes coupled from a TFBG were split into two sets of polarization dependence cladding modes (TE and TM mode) [3,[18][19][20]. In addition to TFBGs, there were also several papers which have given theoretical modeling about the transmission spectra of tilted gratings with long period pattern [21,22]. Recently, Mou et al have published a review chapter about sensing applications using Ex-TFGs [23], and we have reported a high Q factor and sensitivity glucose sensor by using an Ex-TFG [24].…”
Section: Introductionmentioning
confidence: 99%
“…Because of scattering losses, the light coupled to the cladding modes decays fast in the guided core mode observed at the output end of LPFG [19,20]. Therefore, transmission spectrum of this type of filter has a series of attenuation bands which are employed for the ripple compensation in EDF gain.…”
Section: Introductionmentioning
confidence: 99%